2006
DOI: 10.1016/j.rmed.2005.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A simple laboratory measurement for discrimination of transudative and exudative pleural effusion: Pleural viscosity

Abstract: We have demonstrated for the first time that pleural viscosity of the exudative effusion is higher than that of transudative effusion with high sensitivity, specificity, positive and negative predictive value. Regarding the simplicity of this measurement, it may play a valuable role in the accurate and fast discrimination of pleural fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…To our knowledge, these are the first data in the literature to suggest a diagnostic utility for ascitic fluid viscosity measurement. In a Turkish study, Yetkin et al (6) reported that the viscosity of pleural exudative effusions was higher than that of transudative pleural effusions, with high sensitivity. The increment of total protein and albumin concentrations in infected pleural fluid could explain the increased pleural viscosity.…”
Section: Roc Curvementioning
confidence: 98%
See 1 more Smart Citation
“…To our knowledge, these are the first data in the literature to suggest a diagnostic utility for ascitic fluid viscosity measurement. In a Turkish study, Yetkin et al (6) reported that the viscosity of pleural exudative effusions was higher than that of transudative pleural effusions, with high sensitivity. The increment of total protein and albumin concentrations in infected pleural fluid could explain the increased pleural viscosity.…”
Section: Roc Curvementioning
confidence: 98%
“…Plasma viscosity is a biochemically composite variable and is influenced by the concentration of plasma proteins and lipoproteins, of which fibrinogen is a major contributor. It has been shown that measuring plasma viscosity is a simple, reliable test, with no significant change in plasma viscosity when samples are stored frozen for up to 12 months (5,6). Additionally, pleural fluid viscosity appears to provide better discrimination between transudative and exudative pleural effusions.…”
Section: Le Rôle De La Viscosité Du Liquide D'ascite Dans Le Diagnostmentioning
confidence: 99%
“…Pleural viscosity has a high sensitivity, and specificity with high positive and negative predictive values for discriminating exudative and transudative pleural effusions. 4 The physico-chemical or rheological approach states that the contribution of individual proteins and lipoproteins to plasma viscosity depends on their concentration, MW, rigidity and asymmetrical shape. 5,6 In this study pleural fluid viscosity was used to discriminate between various aetiologies of exudative effusions such as malignant, parapneumonic, or tuberculous.…”
Section: Introductionmentioning
confidence: 99%
“…Following the diagnosis of a pleural effusion, a critically important step is to determine the etiology of the effusion (Table 1). The differentiation between a transudate or an exudate provides a clue toward differential diagnosis of the pleural effusion (Yetkin, Tek, Kaya, Ciledag, & Numanoglu, 2005).…”
Section: Types Of Pleural Effusionsmentioning
confidence: 99%